2021
DOI: 10.4103/apjon.apjon-2138
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Information Support Program on Self-Efficacy of Prostate Cancer Patients during Hormonal Therapy

Abstract: Objective: This study was conducted to evaluate the effect of an information support program on the self-efficacy (SE) of prostate cancer (PCa) patients receiving hormonal therapy (HT). Methods: Based on the information support program constructed in a previous study, a randomized controlled trial was conducted in a cancer hospital in Shanghai, China. One hundred subjects were randomly divided into two groups. The control group was provided routine care and communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…One study reported on the effect of an information support programme on more than 30 outcomes [ 52 ]. Of those, 24 improved significantly (all p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported on the effect of an information support programme on more than 30 outcomes [ 52 ]. Of those, 24 improved significantly (all p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 24 improved significantly (all p < 0.05). These can be broadly categorised into information acquisition, information assistance, disease knowledge mastery, healthy lifestyle, self-efficacy, positive attitude, self-decision making and healthy behaviour adherence [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, technology-based https://doi.org/10.1017/S0007114522003452 Published online by Cambridge University Press Accepted manuscript solutions have been shown to strengthen the relationship and communication between patients and their doctors, making patients feel more confident and empowered, supporting their active involvement in the process, and improving shared decision-making (37) . A support program for patients with prostate cancer comprising manuals, videos, the internet, social media, and personalised consultation helped to improve information acquisition during hormone therapy and improve the self-efficacy and healthy behaviour adherence of patients (18) .…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of how best to educate PCa patients receiving ADT to adopt nutritional changes and increase physical activity. Many studies have shown that providing adequate information to PCa patients receiving hormone therapy can improve healthy behaviour, self-care ability and QoL ( 16 18 ) . Written information is a cost-effective way to complement physicians’ verbal advice and enables patients to better manage their health, particularly when part of an information support program ( 18 , 19 ) .…”
mentioning
confidence: 99%
“… 14 Presently, interventions aimed at augmenting the symptom self-management capability of patients and caregivers are predominantly conducted by trained healthcare professionals within clinical settings or through home visits, with durations ranging from several weeks to months. 19–25 Although these interventions have proven effective, it is self-evident that their extensive implementation in the existing healthcare landscape poses challenges due to substantial demands on human resources and financial investment. Consequently, the adoption of more cost-effective approaches becomes imperative.…”
Section: Introductionmentioning
confidence: 99%